2019
DOI: 10.1177/0956797619849928
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Evolutionary Mismatch? Why Facial Width-to-Height Ratio May Not Predict Behavioral Tendencies

Abstract: This study contributes to the growing literature linking physical characteristics and behavioral tendencies by advancing the current debate on whether a person’s facial width-to-height ratio (fWHR) predicts a variety of antisocial tendencies. Specifically, our large-scale study avoided the social-desirability bias found in self-reports of behavioral tendencies by capturing survey data not only from more than 1,000 business executives but also from evaluators who reported knowing the focal individuals well. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…The manifestation of aggression has been widely studied by using aggression paradigms [35] and self-report questionnaires [5]. Studies on aggression with self-reported data were argued against an inherent social-desirability bias, and a recent study investigating the relationship between fWHR and aggressiveness was designed to incorporate data collected from the colleagues of the study subjects [34]. However, that study design still carries an intrinsic risk of bias, as the colleagues might hesitate to reveal real opinions on the behavioral characteristics of the subjects studied.…”
Section: Discussionmentioning
confidence: 99%
“…The manifestation of aggression has been widely studied by using aggression paradigms [35] and self-report questionnaires [5]. Studies on aggression with self-reported data were argued against an inherent social-desirability bias, and a recent study investigating the relationship between fWHR and aggressiveness was designed to incorporate data collected from the colleagues of the study subjects [34]. However, that study design still carries an intrinsic risk of bias, as the colleagues might hesitate to reveal real opinions on the behavioral characteristics of the subjects studied.…”
Section: Discussionmentioning
confidence: 99%
“…Among professional mixed martial arts fighters, high-fWHR men have more favorable win-loss records (Třebický et al, 2015;Zilioli et al, 2015). Formidably faced men further exhibit more interpersonal dominance (e.g., Carré & McCormick, 2012;Goetz et al, 2013;Haselhuhn, Ormiston, & Wong, 2015; but see Wang et al, 2019).…”
Section: Masculine Facial Features Connoting Formidabilitymentioning
confidence: 99%
“…Despite evidence implicating high-fWHR as diagnostic of physical prowess, various limitations in utilizing fWHR in affordance judgments have become apparent. Large-sample studies indicate fWHR is unassociated with hostile behavioral repertoires (e.g., Deaner, Goetz, Shattuck, & Schnotala, 2012;Kosinski, 2017;Wang et al, 2019). Discrepancies appear part of a mismatch between ancestral bases of formidability with modern contexts (Li, Van Vugt, & Colarelli, 2018).…”
Section: Masculine Facial Features Connoting Formidabilitymentioning
confidence: 99%
“…Despite this body of evidence, more recent work has called this link between fWHR and physical prowess into question (e.g., Deaner et al, 2012;Kramer, 2015;Özener, 2012;Wang et al, 2019). Conflicting results have led researchers to consider inferences of formidability to emerge as part of an evolutionary mismatch (Durkee & Ayers, 2020;Li et al, 2018).…”
Section: Masculine Facial Features Connoting Formidabilitymentioning
confidence: 99%
“…Wide-faced men are physically strong and masculine, traits that are the product of testosteronization and ultimately attractive to women (Lefevre & Lewis, 2014;Whitehouse et al, 2015). However, for wide-faced men whose facial height produced high-POST-FIGHT AND fWHR 22 fWHR, their self-perceived formidability may calibrate their behavioral repertoire to increase dominance (see Eisenbruch et al, 2015;Lukaszewski & Roney, 2011) in a manner that corresponds with others' perceptions of their prowess based on fWHR's historically important signal value in identifying interpersonal threats (Wang et al, 2019).…”
Section: Social Underpinnings Of Fwhrmentioning
confidence: 99%